Two new species of Simulium (Gomphostilbia) (Diptera, Simuliidae) from peninsular Malaysia, with keys to peninsular Malaysian members of the Simulium ceylonicum species-group - Takaoka, H.; Sofian-Azirun, Mohd; Hashim, R.; Ya'cob, Z. (2011)
Two new species of black flies, Simulium (Gomphostilbia) roslihashimi sp. n. and S. (G.) lurauense sp. n., are described on the basis of reared adult, pupal and larval specimens collected from Peninsular Malaysia. These two new species are placed in the ceylonicum species-group within the subgenus Gomphostilbia. Simulium (G.) roslihashimi sp. n. is most distinctive with the male having almost entirely yellow antennae, and S. (G.) lurauense sp. n. is characterized in the female by having the elongate sensory vesicle and the yellowish-white hairs on the base of the costal vein and on the stem vein, in the male by the greater number of large upper-eye facets and the spindle-shaped hind basitarsi which are much narrower than the hind tibiae and femora and in the pupa by the small terminal hooks. Keys to species of the ceylonicum speciesgroup reported from Peninsular Malaysia are provided for females, males, pupae and mature larvae.